ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) DITINJAU DARI KEPUASAN KERJA INTRINSIK - SUPARNO EKO WIDODO; ARIQ JAKA RAMADHANU (Program Studi Psikologi Fakultas Pendidikan Psikologi Universitas Negeri Jakarta, 2015)
The purpose of this study was to determine the effect of intrinsic job satisfaction on organizational citizenship behavior (OCB). Measurement of variable of organizational citizenship behavior (OCB) using measuring tool from Podsakoff (1997) and for measurement of job satisfaction variable using measuring tool that is Minessota Satisfaction Questionnaire (MSQ).The method of data processing conducted in this study is the method of regression analysis. The result of research conducted is the behavior of citizenship organization (OCB) (Y) has increased one unit, then job satisfaction variable (X) will automatically add 0.365. It can be concluded that there is a positive (+) effect of intrinsic work satisfaction on the behavior of organizational citizenship (OCB). Seen from result of significance test of result of comparation F Counting 52,4 with F Table (1; 71) is 3,90 then result is F Count bigger than F Table. From the comparison of p = 0,000 and the significance level Î± = 0.05, the result is p <Î±. The conclusion is Ho is rejected then, There is influence of intrinsic work satisfaction on the behavior of citizenship organization (OCB) BPM members of all faculties at the State University of Jakarta. Variable self employment satisfaction 24.1% and felt by other factors outside of job satisfaction such as leadership style, personality type, self efficacy, and others.